Q: 2 to the 0 power plus 2 to the 3 power?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

0+0+2=2 2 divided by 3 = 2/3

6x2-4x2+3 = 0 2x2 + 3 = 0 2x2 = -3 x2 = -3 / 2 this equation has imaginary roots x = +sqaureroot (3/2)i , -sqaureroot (3/2)i where i = complex variable

three 2 - 2 = 0 0 x 3 = 0 0 + 3 = 3

Factor it. y(4y - 1)(3y - 2) = 0 y = 0, 1/4, 2/3

43

Related questions

9 is.

0+0+2=2 2 divided by 3 = 2/3

6x2-4x2+3 = 0 2x2 + 3 = 0 2x2 = -3 x2 = -3 / 2 this equation has imaginary roots x = +sqaureroot (3/2)i , -sqaureroot (3/2)i where i = complex variable

It is: 3^2 plus 2^3 = 17 meaning 9 plus 8 = 17

three 2 - 2 = 0 0 x 3 = 0 0 + 3 = 3

7x2-10x+3=0 (7x-3)(x-1)=0

the answer to 2+3+9+9+0=23 that is the professional way sio HA!!!!

Factor it. y(4y - 1)(3y - 2) = 0 y = 0, 1/4, 2/3

43

3,376

4*7*5+7^2-3*0+15 = 140+49-0+15 = 204

It is 0.